The Effect of Job Promotion on Work Motivation: Evidence from PT. Beiersdorf Indonesia - Raharja, Irwan; Firdaus, Zahra; Syahyuni, Dedy (International Journal of Science, Technology & Management, 2022)
Promotional opportunities offered by companies to employees will create a desire for employees to motivate themselves. This study aims to determine the effect of job promotion on employee performance at PT. Beiersdorf Indonesia by using a saturated sample of 50 respondents, where all the population is used as a sample with a significance level of error of 5% and with an r table of 0.284. Data processing is assisted by SPSS version 25 and Microsoft Excel. This study uses quantitative methods where data collection is done by observation, questionnaires, and documentation study methods. The test results showed the correlation coefficient of job promotion to work motivation was 0.699, which means it is strong and in the same direction because it is positive. In addition, the coefficient of determination is 0.488 (48.8%) and the rest (51.2%) is influenced by other factors that are not included in the variables of this study. The regression equation (Y = 7.051 + 0.431X) shows that there is a positive influence between job promotions and employee motivation at PT. Beiersdorf Indonesia.